Effect of introducing human papillomavirus genotyping into real-world screening on cervical cancer screening in China: a retrospective population-based cohort study. (April 2021) - Dong, Binhua; Zou, Huachun; Mao, Xiaodan; Su, Yingying; Gao, Hangjing; Xie, Fang; Lv, Yuchun; Chen, Yaojia; Kang, Yafang; Xue, Huifeng; Pan, Diling; Sun, Pengming
Background: China's Fujian Cervical Pilot Project (FCPP) transitioned cervical cancer screening from high-risk human papillomavirus (HR-HPV) nongenotyping to genotyping. We investigated the clinical impact of this introduction, comparing performance indicators between HR-HPV genotyping combined with cytology screening (HR-HPV genotyping period) and the previous HR-HPV nongenotyping combined with cytology screening (HR-HPV nongenotyping period). Methods: A retrospective population-based cohort study was performed using data from the FCPP for China. We obtained data for the HR-HPV nongenotyping period from 1 January 2012 to 31 December 2013, and for the HR-HPV genotyping period from 1 January 2014 to 31 December 2016. Propensity score matching was used to match women from the two periods. Multivariable Cox regression was used to assess factors associated with cervical intraepithelial neoplasia of grade 2 or worse (CIN2+). The primary outcome was the incidence of CIN2+ in women aged ⩾25 years. Performance was assessed and included consistency, reach, effectiveness, adoption, implementation and cost. Results: Compared with HR-HPV nongenotyping period, in the HR-HPV genotyping period, more CIN2+ cases were identified at the initial screening (3.06% versus 2.32%; p  < 0.001); the rate of colposcopy referral was higher (10.87% versus 6.64%; p  < 0.001); and the hazard ratio of CIN2+ diagnosis was 1.64 (95% confidence interval, 1.43–1.88; p  < 0.001) after controlling for health insurance status and age. The total costs of the first round of screening (US$66, 609 versus US$65, 226; p  = 0.293) were similar during the two periods. Higher screening coverage (25.95% versus 25.19%; p  = 0.007), higher compliance with age recommendations (92.70% versus 91.69%; p  = 0.001), lower over-screening (4.92% versus 10.15%; p  < 0.001), and reduced unqualified samples (cytology: 1.48% versus 1.73%, p  = 0.099; HR-HPV: 0.57% versus 1.34%, p  < 0.001) were observed in the HR-HPV genotyping period. Conclusions: Introduction of an HR-HPV genotyping assay in China could detect more CIN2+ lesions at earlier stages and improve programmatic indicators. Evidence suggests that the introduction of HR-HPV genotyping is likely to accelerate the elimination of cervical cancer in China.